Tertiary care hospital based study of outcome of facet joint triamcinolone injection in combination with lignocaine in chronic low back ache - Ahsan Wani, M.; Islam, Nuzhat ul; Rasool, Akther; Ganaiee, Mushtaq Ahmed (International Surgery Journal, 2019)
Background: The objective of the study was to determine the effectiveness of facet joint triamcinolone steroid injection in combination with lignocaine in chronic low back ache by measuring the reduction of pain intensity. Methods: This descriptive study was conducted at the post graduate Department of Orthopedics, GMC Srinagar, Kashmir from June 2016 to September 2017. All patients with chronic low back ach (for three months or more) meeting the inclusion criteria were included. Pre pain was assessed using visual analog scale (VAS). Under image intensifier each facet joint was be infiltrated with a mixture containing 10 mg of steroid and 2 ml of 1% lidocaine. Follow ups were done at six weeks’ time and improvement was measured using the same grading system(VAS) to confirm the effectiveness of the procedure. Treatment was considered effective if the patient score below 4 on VAS after treatment with facet joint steroid injection. Results: In our study 100 patients with chronic low back ache were analyzed. The mean age was 56 years with SD ±22.91. The percentage of male patients were 52% while 46% were female. Mean duration of low back ache was 8 months with SD ±3.37. Facet joint steroid injection was efficacious in 67% patients and was ineffective in 33% patients. Conclusion: Facet joint steroid injection in combination with lignocaine is effective in reducing chronic backache and discomfort to the patients.